Propriedades mecânicas e eletroquímicas do aço inoxidável AISI 410 goivado com eletrodo de grafita e soldado por arco submerso - Figueiredo, Elvio (Universidade Federal de São Carlos, 2023)
In petrochemical industries, the electric arc gouging process with a graphite electrode is widely used for removing defective welds in carbon steel. It is a fast and simple process compared to grinding, and more economical than plasma gouging. However, for stainless steels, there is limited information in the literature regarding the amount of carbon deposited in stainless steel during gouging, and the risks of intergranular corrosion and loss of mechanical properties. No studies were found addressing the effect of gouging followed by submerged arc welding on ferritic stainless steels. Therefore, the present work aims to evaluate the metallurgical changes and their consequences on the mechanical and electrochemical properties resulting from gouging followed by submerged arc welding with AWS-ER 410 electrode, in AISI 410 stainless steel. The plates, before and after re-welding, were subjected to tensile and impact tests (Charpy). The degree of sensitization of the welded joint was evaluated through the double loop potentiokinetic reactivation technique (DL-EPR) according to ISO 12732, and the susceptibility to intergranular corrosion was tested according to ASTM A763, practice W. The study showed that gouging, even with appropriat parameters, can lead to sensitization. The intergranular corrosion susceptibility test showed the presence of pits in all samples. The potentiokinetic reactivation test showed a high degree of sensitization, above 5%, in samples subjected to gouging and those welded by submerged arc. Submerged arc welding on AISI 410 reduced toughness and increased the degree of sensitization. Therefore, the use of AISI 410 stainless steel subjected to gouging with a graphite electrode and welded by submerged arc is not recommended for use in the petrochemical industry.
Mechanical and electrochemical properties of stainless steel AISI 410 goived with graphite electrode and submerged arc welding
Keywords: Aço inoxidável; Goivagem a arco; Eletrodo de grafita; Susceptibilidade à corrosão; Grau de sensitização; Stainless steel; Arc gouging; Graphite electrode; Corrosion susceptibility; Degree of sensitization; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS